Risk of cervical pre-cancer and cancer in women with multiple sclerosis exposed to high efficacy disease modifying therapies - Bridge, Francesca; Brotherton, Julia M. L.; Foong, Yi; Butzkueven, Helmut; Jokubaitis, Vilija G.; Van der Walt, Anneke (Frontiers in Neurology, 2023)
There is a growing need to better understand the risk of malignancy in the multiple sclerosis (MS) population, particularly given the relatively recent and widespread introduction of immunomodulating disease modifying therapies (DMTs). Multiple sclerosis disproportionately affects women, and the risk of gynecological malignancies, specifically cervical pre-cancer and cancer, are of particular concern. The causal relationship between persistent human papillomavirus (HPV) infection and cervical cancer has been definitively established. To date, there is limited data on the effect of MS DMTs on the risk of persistent HPV infection and subsequent progression to cervical pre-cancer and cancer. This review evaluates the risk of cervical pre-cancer and cancer in women with MS, including the risk conferred by DMTs. We examine additional factors, specific to the MS population, that alter the risk of developing cervical cancer including participation in HPV vaccination and cervical screening programs.